Nanoparticle-Formulated Curcumin Prevents Posttherapeutic Disease Reactivation and Reinfection with Mycobacterium tuberculosis following Isoniazid Therapy - Tousif, Sultan; Singh, Dhiraj Kumar; Mukherjee, Sitabja; Ahmad, Shaheer; Arya, Rakesh; Nanda, Ranjan; Ranganathan, Anand; Bhattacharyya, Maitree; Van Kaer, Luc; Kar, Santosh K.; Das, Gobardhan (Frontiers in Immunology, 2017)
Curcumin, the bioactive component of turmeric also known as “Indian Yellow Gold,” exhibits therapeutic efficacy against several chronic inflammatory and infectious diseases. Even though considered as a wonder drug pertaining to a myriad of reported benefits, the translational potential of curcumin is limited by its low systemic bioavailability due to its poor intestinal absorption, rapid metabolism, and rapid systemic elimination. Therefore, the translational potential of this compound is specifically challenged by bioavailability issues, and several laboratories are making efforts to improve its bioavailability. We developed a simple one-step process to generate curcumin nanoparticles of ~200 nm in size, which yielded a fivefold enhanced bioavailability in mice over regular curcumin. Curcumin nanoparticles drastically reduced hepatotoxicity induced by antitubercular antibiotics during treatment in mice. Most interestingly, co-treatment of nanoparticle-formulated curcumin along with antitubercular antibiotics dramatically reduced the risk for disease reactivation and reinfection, which is the major shortfall of current antibiotic treatment adopted by Directly Observed Treatment Short-course. Furthermore, nanoparticle-formulated curcumin significantly reduced the time needed for antibiotic therapy to obtain sterile immunity, thereby reducing the possibility of generating drug-resistant variants of the organisms. Therefore, adjunct therapy of nano-formulated curcumin with enhanced bioavailability may be beneficial to treatment of tuberculosis and possibly other diseases.